(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Because there are a lot of various applications in the manufacturing industries and technological processes such as wire drawing, paper production and glass-fiber, processing industries of metal and polymer, and so on, movement of incompressible sticky solutions by stretching sheets appealed a significant focus of the investigators. Using the magnetic field of high power in the ionic liquid with low density, conduction normal to magnetic field is transformed to bending of the atomic particles and ions associated with magnetic force lines prior to arising in conflict and a current induced perpendicular with electric and magnetic field which is called Hall Effect. It is measured through the heat or mass transfer analysis in the conditions in which effect of electromagnetic force is powerful. Research of the electrically conducting solution applies in numerous engineering issues like MHD generators, plasma researches, nuclear reactors, geothermal energy extraction and boundary layer control in aero dynamics. Procedure of heat and mass transfer in the free convection movement applies in numerous chemical engineering procedures, cooling device aeronautics and nuclear reactors. Here we will do the exploratory research on the Theory of Heat and Mass Transfer in Magneto hydrodynamics (MHD).